عہدِحاضر میں تہذیب و شائستگی کے تصوّرات اور اسوۂ نبیﷺ : Need and Significance of Social Insightedness for a Walfare Society in the Light of Sirat Al-Nabi ﷺ - Saeed Ul Rehman, (Seerat Studies, 2023)
For centuries Muslim Ummah has been ruling all over the known world due to its academic excellence, statesmanship, economic and military power. But after 17th century (H.D). The Muslim Ummah gradually started moving towards its decline. On the other side, the western civilization captured the horizon of the world. It was the beginning of the 19th century, when the Muslims around the world went under the influence of the western civilization. The values and traditions of Islamic civilization was considered as hackneyed both mentally and practically. In Turkey, due to the impact of Ataturk and in the sub-continent due to the influence of English imperialism, the Muslims started to imitate western civilization in its dress, food, dialect, values and way of living etc. Western values and traditions became benchmark of decency and courtesy. In the contemporary era, modern means of communication have played a negative role in this respect. Women are exposed in western dress which does not cover the body. TV Drama, commercials and in various other programs, female-sex has become only a show-piece. Oriental traditions are openly criticized. On the other hand, Islam teaches its followers a life based on decency and discipline in all works of life under Seerat-un-Nabi (S.A.W). For the purification of thoughts, Islamic faiths play an important role and for the spiritual expurgation of body and soul, Islamic system of prayers play a vital role. Islam provides a comprehensive teachings in all affairs of life including dress, dialect, and dealing. This research article throws light on the best example set by Prophet Muhammad (PBUH). It not only gives us the leading roles in establishing decency and decorum in a balanced way in our lives but also ensures the formation of a welfare society